The Impact of Haze on Healthcare Utilizations for Acute Respiratory Diseases: Evidence From Malaysia - Jaafar, Hafiz; Azzeri, Amirah; Isahak, Marzuki; Dahlui, Maznah (Frontiers in Ecology and Evolution, 2021)
Haze imposes a substantial disease burden on the human population especially in the Southeast Asia region due to the high frequency of haze episodes. The reduction of air quality levels by haze has resulted in a substantial disease burden and an increase in healthcare utilisation (HU). This study aims to determine the association between haze and HU of haze-related respiratory illnesses with a focus given on the acute exacerbation of bronchial asthma (AEBA) and chronic obstructive pulmonary disease (AECOPD). A cross-sectional study was conducted through secondary data collection of haze/non-haze episodes as the study exposures and HU related to the exacerbation of bronchial asthma and COPD as the study outcomes. Data on haze/non-haze episodes and HU for four consecutive years (2012-2015) were retrieved from the Department of Environment and Ministry of Health Malaysia respectively. In the four consecutive years, the percentage of haze episodes recorded in all stations was higher (67%) as compared to non-haze (33%) episodes. Means (SD) of patients diagnosed with AEBA and AECOPD were also significantly higher (p<0.05) for inpatient 74(62.1) and outpatient 320(650.1) cases during haze episodes as compared to inpatient 34(16.5) and outpatient 146(170.5) cases during non-haze episodes. Findings from this study indicated that haze episodes incurred a significant healthcare burden due to an increase in HU. The evidence from this study will help the policymakers to prepare and allocate resources to control future implications of haze-related illnesses.